The NMR‐based characterization of the FTY720‐SET complex reveals an alternative mechanism for the attenuation of the inhibitory SET‐PP2A interaction. Issue 6 (27th March 2019) - De Palma, Ryan M.; Parnham, Stuart R.; Li, Yitong; Oaks, Joshua J.; Peterson, Yuri K.; Szulc, Zdzislaw M.; Roth, Braden M.; Xing, Yongna; Ogretmen, Besim
ABSTRACT: The su(var)3‐9, enhancer of zeste, trithorax (SET)/inhibitor 2 of protein phosphatase 2A (PP2A) oncoprotein binds and inhibits PP2A, composed of various isoforms of scaffolding, regulatory, and catalytic subunits. Targeting SET with a sphingolipid analog drug fingolimod (FTY720) or ceramide leads to the reactivation of tumor suppressor PP2A. However, molecular details of the SET‐FTY720 or SET‐ceramide, and mechanism of FTY720‐dependent PP2A activation, remain unknown. Here, we report the first in solution examination of the SET‐FTY720 or SET‐ceramide complexes by NMR spectroscopy. FTY720‐ceramide binding resulted in chemical shifts of residues residing at the N terminus of SET, preventing its dimerization or oligomerization. This then released SET from PP2ACα, resulting in PP2A activation, while monomeric SET remained associated with the B56γ. Our data also suggest that the PP2A holoenzyme, composed of PP2A‐Aβ, PP2A‐B56γ, and PP2ACα subunits, is selectively activated in response to the formation of the SET‐FTY720 complex in A549 cells. Various PP2A‐associated downstream effector proteins in the presence or absence of FTY720 were then identified by stable isotope labeling with amino cells in cell culture, including tumor suppressor nonmuscle myosin IIA. Attenuation of FTY720‐SET association by point mutations of residues that are involved in FTY720 binding or dephosphorylation of SET at Serine 171, enhanced SET oligomerization and the formation of the SET‐PP2A inhibitory complex, leading to resistance to FTY720‐dependent PP2A activation.—De Palma, R. M., Parnham, S. R., Li, Y., Oaks, J. J., Peterson, Y. K., Szulc, Z. M., Roth, B. M., Xing, Y., Ogretmen, B. The NMR‐based characterization of the FTY720‐SET complex reveals an alternative mechanism for the attenuation of the inhibitory SET‐PP2A interaction. FASEB J. 33, 7647–7666 (2019). www.fasebj.org